Methoxetamine: A foe or friend?. (January 2019) - Botanas, Chrislean Jun; de la Peña, June Bryan; Kim, Hee Jin; Lee, Yong Sup; Cheong, Jae Hoon
Abstract: Methoxetamine (MXE) is an N -methyl-D-aspartate (NMDA) receptor antagonist that is chemically and pharmacologically similar to other dissociative substances, such as ketamine and phencyclidine. There are reports on the misuse of MXE, which sometimes resulted in adverse consequences and death. Studies have also shown that MXE has abuse liability and stimulates dopamine neurotransmission in the mesolimbic reward pathway in the brain. These findings have contributed to the negative impression on MXE. However, recent preclinical studies have identified the antidepressant properties of MXE, which are attributed to its ability to affect the glutamatergic and serotonergic systems. MXE is also reported to have analgesic effects. These findings show some of the "redeeming qualities" of MXE and indicate its possible therapeutic uses. In this paper, we have reviewed the findings that provide insights into the adverse and potential therapeutic effects of MXE. We compiled studies on the toxicity, psychotomimetic effects, and abuse liability of MXE, as well as its promising antidepressant and analgesic properties. We also have discussed the mechanism of action that might mediate the somewhat paradoxical effects observed. Importantly, this review provides valuable information on MXE for future research and will enable a better understanding of its psychopharmacological properties and the mechanisms responsible for its unique effects. Highlights: We review the adverse and potential therapeutic effects of methoxetamine (MXE). MXE, a structural analogue of ketamine, is an NMDA receptor antagonist. MXE produces toxic and dissociative effects and has abuse liability. MXE also has antidepressant and analgesic properties like ketamine. MXE can affect the dopaminergic, glutamatergic, and serotonergic system.